EX-Ante Carbon balance Tool (EX-ACT) - Food and Agriculture Organization of the United Nations (2015)
The Ex-Ante Carbon-balance Tool (EX-ACT) is an appraisal system developed by FAO providing estimates of the impact of agriculture and forestry development projects, programmes and policies on the carbon-balance. The carbon-balance is defined as the net balance from all greenhouse gases (GHGs) expressed in CO2 equivalent that were emitted or sequestered due to project implementation as compared to a business-as-usual scenario.